The Influences of Corporate Social Responsibility on Firm Performance Measured by Balanced Scorecard: An Evidence of Hotel in Thailand's Southern Border Provinces - Suttipun, Muttanachai; Srirat, Tusneem; Samang, Nusrreya; Manae, Nasree; Maithong, Apitchaya (ABAC ODI JOURNAL Vision. Action. Outcome, 2018)
The study aimed to investigate the extent and level of corporate social responsibility and firm performance measured by balanced scorecard of hotels in Thailand’s Southern border provinces, and to examine the influences of corporate social responsibility and firm performance measured by balanced scorecard. Population was the hotels in the five Southern boarder provinces of Thailand. By simple random sampling, 130 hotels were used as the sample of this study. Descriptive analysis and multiple regression were used to analyze in this study. The findings indicated that corporate social responsibility in terms of consumer, fair operation, employee, and environment were at a high level, while society and community was at a moderate level. Performance measured by balanced scorecard of hotels in the five Southern boarder provinces of Thailand was at a high level. Moreover, employee, environment, and society and community responsibilities had a positive significant influence on the corporate performance, while there was a negative significant influence of hotel age on the corporate performance measured by balanced scorecard.